The Web-Based Learning Environment: A Comparative Study Between The Constructivist And Content-Based Approaches. - Murugiah, Puvaneswary; Atan, Hanafi; Samsudin, Dianne Szalina; M Idrus, Rozhan (2004)
This article reports on the investigation into the differences in students' perceptions when they are subjected to two different instructional designs of the Web-based Learning Environments (WBLEs).